The Challenges of Teaching English for Business: A Case Study at LPP Quantum - Sam Bahri, Muhammad; Bahing; Arina Luardini, Maria (PROJECT (Professional Journal of English Education), 2025)
This article investigates the challenges faced in teaching English for Business (EFB) to students taking a vocational education program at LPP Quantum, one of the vocational education institutions in Sampit City. This study uses a qualitative approach with data collection techniques in the form of in-depth interviews, direct classroom observations, and analysis of learning documents to obtain a comprehensive picture of the problems that arise in the teaching process. The results of the study reveal a number of significant obstacles, such as limited English vocabulary relevant to the business world, low motivation to learn among students, lack of initial understanding of the business context, and limited learning support facilities available. These factors collectively affect the effectiveness and success of teaching Business English in the context of vocational education. Therefore, this study recommends the need for the implementation of a more adaptive, contextual, and responsive pedagogical approach to students' needs, as well as the importance of institutional support in creating a conducive and industrially relevant learning environment.